FACTORS THAT INFLUENCE THE IMPLEMENTATION OF SUSTAINABLE SAFETY AND HEALTH PRACTICES IN THE UPSTREAM SECTOR OF THE NIGERIAN OIL AND GAS INDUSTRY - Zannah Alhaji Ali; Mohd Saidin Misnan (ASEAN Engineering Journal, 2026)
This study analyses the factors influencing the implementation of sustainable safety and health practices within the Nigerian oil and gas industry. Basically, the study focused on examining organizational commitment, communication strategies, training programs, cultural factors, and human behaviour regarding safety and health practices. This research used a quantitative methodology and questionnaires was administered to 330 experienced employees within the oil and gas industry in the Niger Delta region of Nigeria who were purposefully selected as respondents. SPSS, a social sciences statistical tool was used for data analysis using descriptive statistics and structural equation modelling to establish relationships among the identified variables. The research findings point to the fact that cultural factors and human behaviour have a direct impact on safety practices, considering that the coefficient was found to be β = 0.54 and p < 0.05 indicates a strong significant relationship. On the other hand, communication strategies indicated a positive but insignificant effect on safety practices with β = 0.20 and p > 0.05 respectively while training programs also depicted a positive but insignificant effect with β = 0.05 and p > 0.05 respectively. This shows that while they are essential, communication and training alone cannot develop a healthy safety culture in the organization. Thus, the study concludes that cultural factors and human behaviour become the most significant factors influencing sustainable safety and health practices. Hence, it is suggested that organizations should pay more attention to the development of safety culture in compliance with cultural norms and values besides improving communication and training activities to be more appealing to the workers. Future training programs should include cultural sensitivity to remind the workers of safety measures adequately.